A Novel Gene Mutation of Runx2 in Cleidocranial Dysplasia - 彭友俭;陈巧云;付东杰;刘志明;毛甜甜;李俊;佘文婷 (Current medical science, 2017)
Haploinsufficiency of the runt-related transcription factor 2（Runx2） gene is widely known to be responsible for cleidocranial dysplasia（CCD）. To date, more than 190 mutations in Runx2 gene have been reported to be related to CCD. In this study, a novel mutation of Runx2 gene was observed in a female with CCD. Genomic DNA was extracted from peripheral venous blood of the proband and eleven members of her family. Genetic testing on these twelve people identified a novel missense mutation（c.895 T〉C, Y299 H） in exon 5 of the RUNX2 gene in the proband. This mutation results in an amino acid change at codon 895（P.Tyr 299 His.） from a tryptophan codon（TAT） to a histidine codon（CAT）. Our finding may further extend the known mutation spectrum of the RUNX2 gene, and facilitate prenatal genetic diagnosis of CCD in the future.